2009
DOI: 10.1002/anie.200900600
|View full text |Cite
|
Sign up to set email alerts
|

Epoxide‐Opening Cascades in the Synthesis of Polycyclic Polyether Natural Products

Abstract: The group of polycyclic polyether natural products is of special interest due to the fascinating structure and biological effects displayed by its members. The latter includes potentially therapeutic antibiotic, antifungal, and anticancer properties, as well as extreme lethality. The polycyclic structural features of this family can, in some cases, be traced to their biosynthetic origin, but in others that are less well understood, only to proposed biosynthetic pathways that feature dramatic, yet speculative, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
96
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 212 publications
(96 citation statements)
references
References 299 publications
(392 reference statements)
0
96
0
Order By: Relevance
“…The synthesis of polyether natural products has provided some classic examples in this regard. [63] A superb example is Corey and coworkers' recent and remarkably short, enantioselective synthesis of (þ)-omaezakianol (Scheme 5). [64a] A five-fold asymmetric epoxidation of chlorohydrin 1 generates penta-epoxide 2, which, upon treatment with camphorsulfonic acid, undergoes a spectacular substratecontrolled five-fold polycyclisation sequence to generate [42] Pronin.…”
Section: One-component Domino Reactionsmentioning
confidence: 99%
“…The synthesis of polyether natural products has provided some classic examples in this regard. [63] A superb example is Corey and coworkers' recent and remarkably short, enantioselective synthesis of (þ)-omaezakianol (Scheme 5). [64a] A five-fold asymmetric epoxidation of chlorohydrin 1 generates penta-epoxide 2, which, upon treatment with camphorsulfonic acid, undergoes a spectacular substratecontrolled five-fold polycyclisation sequence to generate [42] Pronin.…”
Section: One-component Domino Reactionsmentioning
confidence: 99%
“…Indeed, since Cane-Celmer-Westley's mechanistic proposal for the biosynthesis of polyether ionophores, 10 epoxide opening cascades have become increasingly studied in synthetic organic chemistry as an elegant way to access poly-THF structures. 11 For example, Marshall et al reported a zinc-mediated cascade cyclization of a triepoxide, allowing the access to bis-THF in moderate to good yields (Scheme 1). 12,13 This process allows control of all the stereocenters upstream set by Sharpless and Shi epoxidation reactions and was successfully applied to the synthesis of C17-C32 fragment of Ionomycin.…”
Section: Thf Synthesis By C-o Bond Formation 1 Epoxide Openingmentioning
confidence: 98%
“…3b) provide a justified obstacle to proving or disproving this biosynthetic hypothesis. The kinetic preference for epoxide-opening cascades lies in favor of the exo products, instead of the endo moieties of the ladder poly cyclic ethers 39 . Directing epoxide-opening cascades toward the endo products in the laboratory is made more complex by the inclusion of methyl groups at the ring junctions-seen in every member of the family 40 .…”
Section: Overturning Chemical 'Rules'mentioning
confidence: 99%